2014
DOI: 10.1097/inf.0000000000000233
|View full text |Cite
|
Sign up to set email alerts
|

Periostin is Upregulated in Coronary Arteriopathy in Kawasaki Disease and is a Potential Diagnostic Biomarker

Abstract: Periostin was upregulated 11-fold in acute and chronic KD coronary arteries compared with controls (p=0.003). KD patients had significantly elevated serum periostin values compared with febrile controls (p=0.0086). There was no relationship between serum periostin values and age, gender, or acute phase reactants; there was a relationship between serum periostin and maximal coronary artery Z scores that did not reach significance (p=0.08). Periostin may prove to be useful as a component of a future diagnostic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…PCR assays confirmed significant upregulation of CD74, CD69, IL18, HLA-F, NLRC5, and CD226, genes involved in antigen presentation and dendritic cell function, in KD CA tissues (Additional file 1 : Table S4). Genes that we previously identified as upregulated by real-time PCR on KD and control CA, including CD84, PIM2, POSTN, IL10RA, IL2RA, IQGAP2, and ITGA4 [ 26 28 ] were also identified as significantly upregulated by this transcriptome analysis, providing additional validation of our results.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…PCR assays confirmed significant upregulation of CD74, CD69, IL18, HLA-F, NLRC5, and CD226, genes involved in antigen presentation and dendritic cell function, in KD CA tissues (Additional file 1 : Table S4). Genes that we previously identified as upregulated by real-time PCR on KD and control CA, including CD84, PIM2, POSTN, IL10RA, IL2RA, IQGAP2, and ITGA4 [ 26 28 ] were also identified as significantly upregulated by this transcriptome analysis, providing additional validation of our results.…”
Section: Resultssupporting
confidence: 82%
“…The other 80 proteins are candidate diagnostic/prognostic biomarkers of KD arteritis; such biomarkers are urgently needed for diagnosis and monitoring of KD patients. We have previously reported one of the upregulated proteins, periostin, as a potential diagnostic biomarker of KD [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study also showed that periostin is significantly elevated in KD arteriopathy in both acute (within 2 months after onset) and chronic (5 months to years after onset) patients. 36 Plasma periostin along with periostin and Delta-like Notch ligand 1(DLL1) were higher in patients with severe dilated cardiomyopathy and showed positive correlation with degree of diastolic dysfunction.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Periostin is a matricellular protein that mediates responses associated with cardiovascular injury. Reindel et al (44) have shown that periostin gets upregulated in coronary arteries during the acute and chronic phases of KD when compared to other febrile controls. Gamma-glutamyl transferase (GGT) and alanine transferase (ALT) have also been studied as biomarkers of cardiac inflammation.…”
Section: Proteomic Biomarkers (Table 3)mentioning
confidence: 99%